2019
DOI: 10.1172/jci124466
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody targeting BDCA2 ameliorates skin lesions in systemic lupus erythematosus

Abstract: BACKGROUND. Plasmacytoid DCs (pDC) produce large amounts of type I IFN (IFN-I), cytokines convincingly linked to systemic lupus erythematosus (SLE) pathogenesis. BIIB059 is a humanized mAb that binds blood DC antigen 2 (BDCA2), a pDC-specific receptor that inhibits the production of IFN-I and other inflammatory mediators when ligated. A first-in-human study was conducted to assess safety, tolerability, and pharmacokinetic (PK) and pharmacodynamic (PD) effects of single BIIB059 doses in healthy volunteers (HV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(134 citation statements)
references
References 41 publications
0
131
0
3
Order By: Relevance
“…Although trials targeting TLRs have yielded inconclusive results, a recent study looking at the attenuation of pDC response using an antibody that targets the human pDC-specific BDCA2 in systemic lupus erythematosus (SLE) patients suggests that pDCs are responsible, at least partially, for the presence of the chronic IFN signature in the blood of patients (Furie et al, 2019). Interestingly, blocking pDCs in these patients had a dramatic effect on the skin, with a sustained inhibition of IFNinducible markers in the skin of patients that correlated with amelioration of symptoms (Furie et al, 2019).…”
Section: Origin and Source Of Ifn-i In Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although trials targeting TLRs have yielded inconclusive results, a recent study looking at the attenuation of pDC response using an antibody that targets the human pDC-specific BDCA2 in systemic lupus erythematosus (SLE) patients suggests that pDCs are responsible, at least partially, for the presence of the chronic IFN signature in the blood of patients (Furie et al, 2019). Interestingly, blocking pDCs in these patients had a dramatic effect on the skin, with a sustained inhibition of IFNinducible markers in the skin of patients that correlated with amelioration of symptoms (Furie et al, 2019).…”
Section: Origin and Source Of Ifn-i In Patientsmentioning
confidence: 99%
“…Thus, focusing on the skin to evaluate pDC-targeting drugs would take advantage of a strong scientific rationale and less complex clinical designs. The recent report showing that attenuation of pDCs using BIIB059, a humanized mAb that binds the pDC marker BDCA2, led to reduced IFN signals and cellular infiltration in skin lesions with decreased CLASI-A score (Furie et al, 2019) is a strong indication that an organ-specific approach with a primary focus on the skin may be a promising strategy with such drugs. One can argue that pDCs can be defined as "professional adjuvant cells," which would explain the potent adjuvant effect of CpG-containing oligonucleotides in humans.…”
Section: Role Of Pdc In Hiv-1 Infection and Pathogenesis In Humanizedmentioning
confidence: 99%
“…BDCA2 signals through an associated transmembrane adaptor, the FcϵRγ, which recruits the protein tyrosine kinase Syk, inducing protein tyrosine phosphorylation and calcium mobilization [17] , which, in turn, interferes with TLR induced activation of pDC, inhibiting type I IFN secretion and other inflammatory mediators [15,[17][18][19]. For this reason, antibodies binding BDCA2 have been explored for their potential to block pDC activation in some IFN-associated autoimmune conditions, such as Systemic lupus erythematosus (SLE) [20,21]. Recently, Ah Kioon and colleagues suggested that this could also be applicable to fibrotic disease such as SSc as mouse pDC enhance pathogenesis of bleomycininduced skin fibrosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…These and similar mechanistic studies cited in the paper help inform the rationale for the development of a humanized BDCA-2-binding mAb (BIIB059). Furie et al conducted a multicenter, randomized, double-blind, placebo-controlled phase 1b study (18) assessing the safety, tolerability, pharmacokinetic, and pharmacodynamic effects of BIIB059 in healthy volunteers and patients with SLE with active cutaneous disease. The authors also evaluated the biological activity and clinical response among these cutaneous lupus patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above referenced studies, a unique means of inhibiting the production of type 1 IFN at the level of the plasmacytoid DCs (pDCs) ( Figure 1) was undertaken by Furie et al (18) and reported in this issue. We know that pDCs are the primary cell source of the type 1 IFN signal in SLE.…”
mentioning
confidence: 99%